Biomechanical Analysis of a Novel Double-Point Fixation Method for Displaced Intra-Articular Calcaneal Fractures - Lv, Miko Lin; Ni, Ming; Sun, Wanju; Wong, Duo Wai-Chi; Zhou, Shuren; Jia, Yongwei; Zhang, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
The development of minimally invasive procedures and implant materials has improved the fixation strength of implants and is less traumatic in surgery. The purpose of this study was to propose a novel “double-point fixation” for calcaneal fractures and compare its biomechanical stability with the traditional “three-point fixation.” A three-dimensional finite element foot model with a Sanders type IIIAB calcaneal fracture was developed based on clinical images comprising bones, plantar fascia, ligaments, and encapsulated soft tissue. Double-point and three-point fixation resembled the surgical procedure with a volar distal radius plate and calcaneal locking plate, respectively. The stress distribution, fracture displacement, and change of the Böhler angle and Gissane’s angle were estimated by a walking simulation using the model, and the predictions between the double-point and three-point fixation were compared at heel-strike, midstance, and push-off instants. Double-point fixation demonstrated lower bone stress (103.3 vs. 199.4 MPa), but higher implant stress (1,084.0 vs. 577.9 MPa). The model displacement of double-point fixation was higher than that of three-point fixation (3.68 vs. 2.53 mm). The displacement of the posterior joint facet (0.127 vs. 0.150 mm) and the changes of the Böhler angle (0.9° vs. 1.4°) and Gissane’s angle (0.7° vs. 0.9°) in double-point fixation were comparably lower. Double-point fixation by volar distal radius plates demonstrated sufficient and favorable fixation stability and a lower risk of postoperative stress fracture, which may potentially serve as a new fixation modality for the treatment of displaced intra-articular calcaneal fractures.